Screening of hepatitis C NS5B polymerase inhibitors containing benzothiadiazine core: a steered molecular dynamics. Issue 8 (11th June 2017) - Nutho, Bodee; Meeprasert, Arthitaya; Chulapa, Methat; Kungwan, Nawee; Rungrotmongkol, Thanyada
Abstract : Hepatic C virus (HCV) is a global health problem, resulting in liver cirrhosis and inflammation that can develop to hepatocellular carcinoma and fatality. The NS5B polymerase of HCV plays an important role in viral RNA replication process, making it an attractive therapeutic target for design and development of anti-HCV drugs. To search new potent compounds against the HCV NS5B polymerase, the molecular docking and the steered molecular dynamics (SMD) simulation techniques were performed. The potential potent inhibitors of the NS5B polymerase were screened out from the ZINC database using structural similarity search and molecular docking technique. Five top-hit compounds (the ZINC compounds49888724, 49054741, 49777239, 49793673, and49780355 ) were then studied by the SMD simulations based on the hypothesis that a high rupture force relates to a high binding efficiency. The results demonstrated that the ZINC compound49888724 had a greater maximum rupture force, reflecting a good binding strength and inhibitory potency than known inhibitors and the rest four ZINC compounds. Therefore, our finding indicated that the ZINC compound49888724 is a potential candidate to be a novel NS5B inhibitor for further design. Besides, the van der Waals interaction could be considered as the main contribution for stabilizing the NS5B-ligand complex.